Studies of the Neuroimmune Response in Cancer-Induced Pain - Miladinovic, Tanya (My University, 2019)
Cancer-induced pain (CIP) is a debilitating condition that accompanies late-stage cancer for the majority of patients. The work presented in this dissertation addresses the multifaceted role of glutamate in cancer cell-induced pain signalling and provides several potential therapeutic directions. Several cell types, including breast cancer cells and microglia, release glutamate via the system xC- antiporter. To limit the excitotoxic tendency of breast cancer cells to release glutamate in excess, we first indirectly inhibited xCT, the active subunit of system xC-, with the TrkA inhibitor AG879. We demonstrated that the system xC- antiporter is functionally influenced by the actions of nerve growth factor on its cognate receptor, TrkA, and that inhibiting this complex reduced CIP via downstream actions on xCT. Co-culture studies then demonstrated the direct effect of glutamate released by wildtype MDA-MB-231 carcinoma cells on microglial activation, as well as functional system xC- activity, while knockdown of xCT in MDA-MB-231 cells mitigated microglial activation and cystine uptake. Blockade of system xC- with sulfasalazine attenuated nociception in an immunocompetent murine model of CIP and inhibited tumour-induced microglial activation in the dorsal horn of the spinal cord. Finally, tumour-induced nociceptive behaviours appeared to progress in parallel with microglial activation in the hippocampus, and ablating microglia delayed the onset and severity of tumour-induced nociceptive behaviours, confirming that microglia are implicated in CIP and regional microglia are influenced by this pain. This is the first experimental evidence to demonstrate the effects of peripheral tumour on hippocampal microglial activation in relation to cancer-related nociception. These data collectively demonstrate that the system xC- antiporter is functionally implicated in CIP and may be particularly relevant to pain progression through spinal microglia. Upregulated xCT in chronically activated microglia may be one pathway to central glutamate cytotoxicity. Therefore, microglial xCT may therefore be a valuable target for mitigating CIP.
Keywords: cancer; pain; System xC-; glutamate; microglia; neurotrophin